The management of pediatric obesity and diabetes - Ferry, Robert J. (Robert Jean) Jr. (Totowa, New Jersey Humana, 2011)
The twin epidemics of obesity and type 2 diabetes mellitus (T2DM) continue to affect an ever increasing number of children, adolescents, and young adults. Management of Pediatric Obesity and Diabetes provides healthcare trainees and professionals with practical, comprehensive, and contemporary approaches to the pediatric patient at risk for obesity, T2DM, and related conditions. A unique guide on the subject, this volume provides clinical paradigms for diagnosis and management of pediatric T2DM and related conditions, while succinctly describing state-of-the-art basic and clinical sciences underlying these problems. The chapters in this volume are independent and concise. Each chapter focuses on a key clinical issue or mechanism of disease. Providing practical, data-driven resources based upon the totality of the evidence, this important text helps the reader understand the basics of pediatric obesity and T2DM and implement strategies to prevent and treat obesity and diabetes in children and adolescents. Management of Pediatric Obesity and Diabetes provides health professionals across many areas of research and practice with up-to-date, well-referenced, and comprehensive evidence on identification, treatment, and prevention of these chronic, serious, metabolic diseases in children. This volume will serve the reader as the most authoritative resource in the field to date.
Section I: Definitions of Pediatric Obesity and Diabetes -- 1. Genetics of Obesity, Tetyana L. Vasylyeva -- 2. Fetal Origin of Obesity and Diabetes, Natalia Schlabritz-Lutsevich, Gene Hubbard, Ronald Adkins -- 3. Beta-Cell Growth Mechanisms, Thomas L. Jetton, Dhananjay Gupta, Mina Peshavaria -- 4. Race/Ethnic and Socioeconomic Disparities in Body Mass Index (BMI) and the Resulting Spread of Obesity and "Adult-Onset" Diabetes Epidemics Among Adoloscents, Katherine E. Neubecker -- Section II: Obesity - Clinical Assessments -- 5. Assessment and Treatment of Cardiovascular Disease in Obese Children, Piers R. Blackett, Petar Alaupovic, Kenneth C. Copeland -- 6. Community-based Approaches to Reduce Pediatric Obesity, Keith L. Perkins, Dawn M. McNamee -- 7. Physical Activity Approaches to Pediatric Weight Management, Douglas L. Hill, Brian H. Wrotniak, Kathry,  H. Schmitz -- 8. Behavior Modification in Pediatric Obesity, Gerri Minshall, Fiona Davies, Louise A. Baur -- 9. Surgical Approaches to Pediatric Obesity, Aayed R. Al-Qahtani -- Section III: Diabetes - Clincial Assessments -- 10. Epidemiology of Type 2 Diabetes Mellitus in Pediatric Populations, Shreepal M. Shah -- 11. Nutrition for the Diabetic Child, Catherine M. Champagne -- 12. Pharmacologic Approaches to Type 2 Diabetes and Obesity in Children and Adoloscents, Patama Pongsuwan -- 13. Insulin Pump Management, Justin M. Gregory -- 14. Hyperglycemic Crises in Diabetes Mellitus: Diabetic Ketoacidosis and Hyperglycemic Hyperosmolar State, Dwain E. Woode, Abbas E. Kitabchi -- 15. Monogenic Diabetes, Rabia Rehman, hooman Oktaei, Dale Childress, Solomon S. Solomon -- 16. Secondary Causes of Obesity in Childhood, Paula Hale, Tulay Cushman, Edward S. Kimball, Aji Nair, Rebecca Gusic Shaffer.
Electronic reproduction.
Keywords: Obesity in children; Diabetes in children; Obesity in children -- Treatment; Diabetes in children -- Treatment; Obesity in children -- Complications